Energy Beverage Use Among U.S. Service Members. Issue 9 (11th July 2018) - Attipoe, Selasi; Delahanty, Liam; Stephens, Mark; Deuster, Patricia A
Abstract: Introduction: The use of energy drinks (ED) or shots (ES) is becoming increasingly popular in U.S. beverage market. In addition, young, physically active males, such as active-duty enlistees represent a prime target for the advertising of ED/ES; however, the exact mechanisms and safety of these products have come under scrutiny. This cross-sectional, exploratory, web-based survey among U.S. service members describes the prevalence of ED/ES use as well as common side effects and safety of these products among self-reported users. Materials and Methods: A convenience sample of U.S. military members ( n = 1, 706; response rate = 7%) was used to conduct a cross-sectional, exploratory, web-based survey of ED/ES usage among U.S. military members. Main outcome measures included: (1) prevalence of ED/ES use, (2) perceived effects associated with use, and (3) differences among subgroups. Results: Among all respondents, 50% reported consuming ED and 16% reported consuming ES at least once a month. Young, male, enlisted and members of operational military units were significantly more likely to indicate use of ED/ES at least once within the past 30 days than other groups, and were more likely to co-ingest ED and alcohol. Self-reported reasons for using ED included needing an energy boost (77%) and increasing mental alertness (52%). Perceived increases in mental alertness, heart rate, and mental endurance were the most commonly reported effects of ED/ES consumption. About a third (36%) perceived energy beverages and dietary supplements to be safe; while more than half (53%) reported not discussing ED, ES, vitamins/minerals, DS, caffeine, or alcohol use with their healthcare provider(s). Conclusion: Military Service members fit the targeted age and gender demographic of many marketing campaigns for ED/ES products, and many perceive these beverages as safe to use. The possible problems associated with overuse/reliance on ED/ES products, particularly relating to operational force readiness, merit further investigation.